MATHEMATICAL MODEL OF MACHINE AGGREGATE OF TILLAGE EQUIPMENT PROCESS - Mamaxonov, A’zam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article, the mathematical model of the Tillage-cultivating unit was obtained. Based on the numerical solution of the system of motion equations of the machine unit, the laws of speed, acceleration and moment changes of the driving sprocket of the pile drum and chain transmission were determined depending on the resistance moment coming from the cutting. The laws of dependence of the average values of the vibration interval of the angular speed, acceleration and torques of the pile drum and the driven sprocket on the resistance moment were studied. Mechanical characteristics of pile drum and chain drive sprocket are determined.